2003
DOI: 10.1111/1467-9507.00250
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gender Context on Children's Social Behavior in a Limited Resource Situation: An Observational Study

Abstract: Knowing when to compete and when to cooperate to maximize opportunities for equal access to activities and materials in groups is critical to children's social and cognitive development. The present study examined the individual (gender, social competence) and contextual factors (gender context) that may determine why some children are more successful than others. One hundred and fifty-six children (M age = 6.5 years) were divided into 39 groups of four and videotaped while engaged in a task that required them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 69 publications
(106 reference statements)
1
11
0
Order By: Relevance
“…Perhaps it is only when children are playing with familiar peers that a child's gender and the gender context become significant predictors of behaviour. The relative lack of interactions between gender and group composition was also surprising in light of the differences found by Green et al (2003) in the amount of viewing time obtained by girls and boys in same-sex and mixed-sex groups. It may be that although gender context influenced the distribution of viewing time among group members, it did not change the strategies that the children used to obtain viewing time.…”
Section: Effects Of Group Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps it is only when children are playing with familiar peers that a child's gender and the gender context become significant predictors of behaviour. The relative lack of interactions between gender and group composition was also surprising in light of the differences found by Green et al (2003) in the amount of viewing time obtained by girls and boys in same-sex and mixed-sex groups. It may be that although gender context influenced the distribution of viewing time among group members, it did not change the strategies that the children used to obtain viewing time.…”
Section: Effects Of Group Compositionmentioning
confidence: 99%
“…However, whether the inequity is partly caused by the types of strategies girls and boys use in each other's presence during cooperative and competitive encounters is not known. Previous research has demonstrated effects of gender group composition on amount of resource use; girls gained in same-sex groups but lost in mixed-sex groups, while the opposite was found for boys (Green et al, 2003). Although evidence suggests that girls and boys adjust their unique interaction styles to the gender of their playmates (Archer, 1992;Maccoby, 1990), no movie-viewer studies have directly examined the effect of gender composition on strategy use.…”
mentioning
confidence: 99%
“…Girls tend to withdraw from social interactions that include boys because they are viewed as too boisterous and dominating. It is not surprising then, that elementary school children may work better in same-gender groups (Green et al 2003).…”
Section: School Levelmentioning
confidence: 99%
“…Perhaps more gender differences will be found if mixed groups are analyzed-this may be a promising avenue for future research. In a study with six-year-old children, Green, Cillessen, Berthelsen, Irving, and Catherwood (2003) found that the gender composition of play groups has a strong impact on children' s cooperative and competitive behavior. For some variables, a mixed-gender context increased gender differences compared to a same-sex environment.…”
Section: New Perspectives On Social Networkmentioning
confidence: 99%